Utilization of integrated HIV and sexual and reproductive health services among women in Uganda - Rutaremwa, Gideon; Kabagenyi, Allen (BMC Health Services Research, 2016)
While the rationale for integration of HIV and sexual and reproductive health (HIV and SRH) services is strong, there is paucity of information on which population groups most utilize these services. Such studies would inform policy and programs on integration of services. The overall objective of this assessment is to provide information to researchers, planners and policy makers on the best practices for integrated services in order to maximize feasibility of scaling up. Specifically, this research paper identifies demographic and socioeconomic factors that are most related to utilization of integrated services in Uganda. Methods: This manuscript uses data from a sample of 9,691 women interviewed during the Uganda AIDS Indicator Survey (UAIS) of 2011. The selection criteria of the study respondents for this paper included women of reproductive age 15 – 49 years. The dependent variable is whether the respondent utilized integrated HIV and SRH services during pregnancy and delivery of the last child, while independent variables include; region of residence, age-group of woman, marital status, rural-urban residence, wealth indicator and educational level attainment. In the main analysis, a binary logistic regression model was fitted to the data. Results: Log-odds of utilizing integrated services were significantly higher among those women with a primary education (OR = 1.2, 95 % CI = 1.0-1.4, p < 0.05) compared to those with no education. Women from the Central part of Uganda were more likely to utilize integrated HIV and SRH services (OR = 1.3, 95 % CI = 1.0-1.7, p < 0.05), further the log-odds of utilizing integrated HIV and SRH services were significantly higher among women residing in Northern region (OR = 1.6, 95 % CI = 1.2-2.2, p < 0.01). The odds of utilization of integrated HIV and SRH services were higher for currently married women (OR = 6.6, 95 % CI = 5.5-8.0, p < 0.01) and the formerly married (OR = 3.4, 95 % CI = 2.7-4.2, p < 0.01), compared to the never married group. The odds of utilizing integrated HIV and SRH services were higher for younger women of ages less than 35 years compared to older women aged 40 – 49 years. Conclusions: Utilization of integrated HIV and SRH services in Uganda is influenced greatly by demographic and socioeconomic characteristics. This study contributes to the current debate as it shows the on how best ways to improve HIV and SRH service delivery to the people.
Keywords: Utilization; Integrated; HIV; Sexual; Reproductive Health; Women and Uganda